Stained glass windows depicting prominent themes from Christianity - Mumbai Archive Project Team (Jio Institute, 2024)
St. Anne’s Church has stained glass windows depicting prominent themes from Christianity. The window in the centre depicts the Ascension of Jesus; the window on the right depicts the Descent of the Holy Spirit; and the one on the left depicts the Coronation of Our Blessed Lady and the Glory of All the Saints.